A 15 U.S. Minimum Wage: How the Fast-Food Industry Could Adjust Without Shedding Jobs. Issue 3 (2nd July 2016) - Pollin, Robert; Wicks-Lim, Jeannette
Abstract: We consider the extent to which U.S. fast-food businesses could adjust to an increase in the federal minimum wage from its current level of 7.25 an hour to 15 an hour without having to resort to reducing their workforce. We consider this issue through a set of simple illustrative exercises, whereby the US raises the federal minimum wage in two steps over four years, first to 10.50 within one year, then to 15 after three more years. We conclude that the fast-food industry could absorb the increase in its overall wage bill without resorting to cuts in their employment levels at any point over this four-year adjustment period. We find that the fast-food industry could fully absorb these wage bill increases through a combination of turnover reductions, trend increases in sales growth, and modest annual price increases over the four-year period. Working from the relevant existing literature, our results are based on a set of reasonable assumptions on fast-food turnover rates, the price elasticity of demand within the fast-food industry, and the industry's underlying trend for sales growth. We also show that fast-food firms would not need to lower their average profit rate during this adjustment period.